Perceptions of Reasonable Use of Force by Probation Officers and Civilians - Sowards, Timothy Loranzy (2018)
There is little academic research that examines whether there are differences between the ways probation officers and community members perceive the use of force on juvenile offenders. Failure to understand the differences in these perceptions negatively affected a probation department in California, which failed to address public concerns regarding the use of force in the juvenile hall, which resulted in a consent decree and a costly financial settlement. Using socialization theory as the foundation, the purpose of this study was to understand if there is a statistically significant difference between probation officers and civilians regarding their perceptions of use of force against juvenile offenders. Data were collected from a nonprobability sample of probation officers (n = 71) and community members (n = 125) in a Northern California community through an online survey that featured 5 scenarios of escalating behavior from a juvenile offender. Respondents were asked to evaluate whether the use of force was appropriate or excessive for each scenario. Data were analyzed using an independent samples t test and chi-square tests of independence. Findings indicated that, overall, there is a statistically significant difference in the perception of use of force between the 2 groups (p <. -4.04). Specifically, community members are more likely to have a lower threshold of tolerance for use of force than probation officers in 3 of the 5 scenarios in the survey. The positive social change implications of this study include recommendations to probation departments in California for enhanced collaboration and training with community members to better understand the expectations of each group related to use of force and the treatment of juvenile offenders